High-performance liquid chromatographic analysis explores the potential antioxidative agents of Argyreia argentea ARN. EX CHOISY extract - Md. Nazim Uddin; Md. Atiar Rahman; Hemayet Hossain; Tanzir Ahmed Khan; Rehana Akter (Wolters Kluwer Medknow Publications, 2019)
Background: Antioxidative properties of medicinal plants play the key role in plant defense mechanism. Argyreia argentea is an evergreen shrub which is used in the treatment of boils, gastric ulcers, tumor, marasmus, paralysis and spermatorrhea, rheumatoid arthritis, cold, painful sensation, and fever. Aims: This research investigates the phytochemical contents and antioxidative effects of optimized crude methanol extract of A. argentea. Materials and Methods: Crude methanol extract of A. argentea prepared in an optimized procedure has been analyzed by high-performance liquid chromatography to quantitatively determine the phytochemical contents. Tannin content of the extract was determined by established method. The extract was also analyzed for in vitro antioxidative actions by spectrophotometric analysis using 2,2'-azino-bis(3-ethylbenzo-thiazoline-6-sulfonic acid) diammonium salt (ABTS) method, N, N-dimethyl-1,4-diaminobenzene (DMPD) free radical scavenging method, superoxide radical scavenging method, and nitric oxide scavenging method. Results: The experimental results showed a high amount of catechin hydrate (348.62mg/100g of dry extract) and moderate amount of gallic acid, p-coumaric acid, and rutin hydrate in the methanol extract of A. argentea. Tannin content was found to be 29.66mg/g tannic acid equivalent. Scavenging effects expressed as inhibition concentrations (IC50) for ABTS assay, DMPD assay, superoxide assay, and NO assay were 1148.3 µg/mL ± 7.32 µmol ascorbic acid/g, 1017.68 µg/mL, 1116.89 µg/mL, 1835.23 µg/mL, respectively. All the values were compared with their respective standards. No β-carotene was detected in the extract. Conclusions: Use of A. argentea extract as a source of functional food as well as an antioxidative agent could be considered with further confirmation.